A Predictive Theory of Mental Evolution and Its Consequences - Steinberg, David A. (Cambridge Scholars Publishing, 2021)
The premise of this book is that the external world can be known only as an internally constructed model. Therefore, a careful analysis of how internal correlates are created can unify and explain disparate and fundamental scientific concerns. Among these are the nature of mathematics, the origin of time, and a predictive theory of mental evolution whose stages culminate in an unambiguous and rigorous definition of consciousness. Validation of this theory's predictions explains the sequence and meaning of Paleolithic Age artifacts and identifies a temporal origin of language. Additional conseq.